Novel carbonized polybenzoxazine aerogel and preparation method thereof

By preparing a new type of carbonized polybenzoxazine aerogel, the weight, cost and secondary electromagnetic pollution problems of existing electromagnetic shielding materials are solved, and the combination of high resistivity and strong electromagnetic shielding performance is achieved, expanding the scope of application.

CN119591084AActive Publication Date: 2025-03-11SHIJIAZHUANG TIEDAO UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411824790.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-11
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The existing electromagnetic shielding materials have weight, cost and secondary electromagnetic pollution problems. At the same time, there is a contradiction between electrical conductivity and electronic thermal conductivity and electromagnetic shielding performance, resulting in poor thermal insulation and thermal insulation capabilities.

Method used

By preparing a new carbohydrate polybenzoxazine aerogel, using bisphenol F-type benzoxazine monomer, N,N-dimethylformamide and hydrochloric acid as raw materials, and using acid-catalytic polymerization and atmospheric pressure drying, an aerogel with high resistivity and strong electromagnetic shielding performance was prepared.

Benefits of technology

It has achieved a combination of high resistivity and strong electromagnetic shielding performance, breaking through the contradiction between electrical/thermal conductivity and electromagnetic shielding performance, and expanding its application scope in fields such as precision electronic devices, aerospace and high-speed network signal transmission.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591084A_ABST
    Figure CN119591084A_ABST
Patent Text Reader

Abstract

The invention discloses a novel carbonized polybenzoxazine aerogel and a preparation method thereof, the novel carbonized polybenzoxazine aerogel is prepared by carbonizing a novel polybenzoxazine aerogel, and the invention belongs to the technical field of aerogel materials. The preparation method comprises the following steps: preparing a polybenzoxazine solution; putting the polybenzoxazine solution into a mold to form wet gel; aging the wet gel, and drying at normal pressure for 24 hours after aging; the aged wet gel is washed with N, N-dimethylformamide, and wet conductive gel is obtained; and drying the wet gel at normal temperature and normal pressure to obtain the novel polybenzoxazine aerogel. The polybenzoxazine aerogel is subjected to heat preservation for 6 hours at the temperature of 800 DEG C in an argon environment to be carbonized, then furnace cooling is carried out, and the novel carbonized polybenzoxazine aerogel is obtained after the polybenzoxazine aerogel is cooled. The preparation method has the advantages that the bisphenol F type benzoxazine monomer is used as a raw material, and the preparation method is simple through acid catalytic polymerization and normal-pressure drying; compared with other aerogel materials, the aerogel disclosed by the invention has excellent electromagnetic shielding performance and relatively high resistivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aerogel materials, and in particular relates to a novel carbonized polybenzoxazine aerogel and a preparation method thereof. Background Art

[0002] Aerogel materials have excellent properties such as ultra-low density, ultra-low thermal conductivity and super sound insulation, and have been widely used in thermal insulation and energy saving, sound insulation, noise reduction and shock absorption and military fields.

[0003] Polybenzoxazine (PBO) aerogel is a new type of thermosetting material with unique performance advantages such as high modulus, high strength, good heat resistance and low water absorption. It has broad application prospects in aerospace thermal protection, aviation structure and flame retardancy, electronic devices and other fields.

[0004] On the other hand, today's increasingly serious electromagnetic pollution and electromagnetic protection problems have made the demand for excellent electromagnetic shielding materials more urgent.

[0005] Generally speaking, the more conductive a material is, the stronger its electromagnetic shielding performance is. This is because the more conductive a material is, the easier it is to form an electrical circuit between materials, absorbing and reflecting electromagnetic waves, thereby improving electromagnetic shielding performance.

[0006] Common electromagnetic shielding materials have a series of problems, such as weight, cost, secondary electromagnetic pollution, etc. At the same time, electrical conductivity and electronic thermal conductivity are related to the movement of electrons inside the material, which will lead to poor thermal insulation capabilities of the material and increase the loss of electronic components.

[0007] The materials with strong electromagnetic shielding performance reported so far generally have low resistivity. Summary of the invention

[0008] The present application provides a method for preparing a novel carbonized polybenzoxazine aerogel. The novel carbonized polybenzoxazine aerogel prepared by the method has high resistivity and strong electromagnetic shielding performance, breaking through the contradiction between electrical / thermal conductivity and electromagnetic shielding performance, and can greatly expand the application scope in the fields of precision electronic devices, aerospace, and high-speed network signal transmission.

[0009] The first object of the present invention is to disclose a novel carbonized polybenzoxazine aerogel.

[0010] The second object of the present invention is to disclose a novel method for preparing carbonized polybenzoxazine aerogel.

[0011] The objective of the present invention is achieved through the following technical solutions:

[0012] A novel carbonized polybenzoxazine aerogel is prepared from the following raw materials in parts by weight: 10-40 parts of bisphenol F-type benzoxazine, 50-200 parts of N,N-dimethylformamide, and 0.5-5 parts of hydrochloric acid, wherein the concentration of the hydrochloric acid is 36%-38%.

[0013] The novel carbonized polybenzoxazine aerogel has a specific surface area of ​​5.38-24.811 square meters per gram, an average pore diameter of 5.95-14.16 nanometers, a resistivity of 4.93-7.34 ohm·meters, and an electromagnetic shielding of 28.05-77.51 decibels for 8-12.4 GHz electromagnetic waves.

[0014] A novel method for preparing carbonized polybenzoxazine aerogel, wherein the preparation method comprises the following steps:

[0015] (1) dissolving bisphenol F type benzoxazine in N,N-dimethylformamide and heating to obtain a bisphenol F solution; adding hydrochloric acid to N,N-dimethylformamide to obtain an acid catalytic solution; mixing the bisphenol F solution and the acid catalytic solution and stirring to obtain a polybenzoxazine solution;

[0016] (2) placing the polybenzoxazine solution obtained in step (1) into a mold to form a wet gel;

[0017] (3) aging the wet gel obtained in step (2), and drying at normal pressure for 24 hours after aging;

[0018] (4) washing the aged wet gel obtained in step (3) with N,N-dimethylformamide to obtain a wet conductive gel;

[0019] (5) drying the wet conductive gel obtained in step (4) at room temperature and pressure for 24-48 hours to obtain a novel polybenzoxazine aerogel having electrical conductivity and electromagnetic shielding properties;

[0020] (6) The polybenzoxazine aerogel obtained in step (5) is heated to 800° C. in an argon environment at a heating rate of 5° C. / min. After heating to 800° C., the aerogel is kept at this temperature for 6 hours and then cooled in a furnace. During the heating and cooling in the furnace, the argon flow rate is ensured to be greater than 50 ml / min. After cooling, a novel carbonized polybenzoxazine aerogel is obtained.

[0021] The above technical solution provides a novel method for preparing carbonized polybenzoxazine aerogel, wherein: in step (1), by weight, bisphenol F-type benzoxazine is 10-40 parts, N,N-dimethylformamide is 50-200 parts, and hydrochloric acid is 0.5-5 parts, and the concentration of hydrochloric acid is 36%-38%.

[0022] The method for preparing a novel carbonized polybenzoxazine aerogel described in the above technical scheme is calculated by weight, wherein: in step (1), 10-30 parts of bisphenol F type benzoxazine are placed in 20-40 parts of N,N-dimethylformamide, and heated in a heating box at 80°C for 12 hours, and cooled to room temperature to obtain a bisphenol F solution; 2-5 parts of concentrated hydrochloric acid are added to 20-40 parts of N,N-dimethylformamide and uniformly stirred to obtain an acid catalytic solution; the acid catalytic solution is added to the bisphenol F solution and rapidly stirred for 30 seconds to obtain a polybenzoxazine solution.

[0023] The method for preparing a novel carbonized polybenzoxazine aerogel described in the above technical solution, wherein: in step (2), the gel time is greater than 15 minutes.

[0024] The above technical solution provides a novel method for preparing carbonized polybenzoxazine aerogel, wherein: in step (3), the aging environment is normal temperature and pressure; and the aging time is 12-24 hours.

[0025] The method for preparing a novel carbonized polybenzoxazine aerogel described in the above technical solution, wherein: in step (4), the wet gel is washed with N,N-dimethylformamide for 1-3 times, and each washing time is 10-20 hours.

[0026] A novel carbonized polybenzoxazine aerogel is prepared by the preparation method described in the above technical solution.

[0027] The novel carbonized polybenzoxazine aerogel described in the above technical solution, wherein: the novel carbonized polybenzoxazine aerogel has a specific surface area of ​​5.38-24.811 square meters per gram, an average pore size of 5.95-14.16 nanometers, a resistivity of 4.93-7.34 ohm·meters, and an electromagnetic shielding of 8-12.4 GHz electromagnetic waves of 28.05-77.51 decibels.

[0028] The present invention has the following beneficial effects:

[0029] 1. The novel carbonized polybenzoxazine aerogel of the present invention uses bisphenol F-type benzoxazine monomer as a raw material and can be prepared by acid-catalyzed polymerization and normal pressure drying. The preparation method of the aerogel is simple and the prepared aerogel has excellent electromagnetic shielding performance.

[0030] 2. In the cleaning process of step (4) of the present invention, N,N-dimethylformamide solution is used to make the reaction of the wet gel more complete and to strengthen the newly formed benzoxazine skeleton structure; impurities are removed, the network structure of the gel is strengthened, the gel is easy to dry, and the gel has better electromagnetic shielding performance.

[0031] 3. Compared with other electromagnetic shielding materials, the present invention has stronger electromagnetic shielding performance, higher resistivity and poorer conductivity.

[0032] 4. Compared with other polybenzoxazine aerogels, the novel carbonized polybenzoxazine aerogel prepared in the present invention has a smaller specific surface area and a smaller average pore size. This porous network structure feature enhances the reflection and scattering of electromagnetic waves, making its electromagnetic shielding effect stronger.

[0033] 5. Step (6) of the present invention adds a carbonization step. After carbonization, the conductivity of the material itself is enhanced, making it easier to form an electrical circuit inside the material to enhance the reflection of electromagnetic waves, thereby further enhancing the electromagnetic shielding capability. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is a comparison chart of the electromagnetic shielding performance of Examples 1-4.

[0035] Figure 2 It is a comparison chart of the electromagnetic shielding performance of Example 4, Example 5 and Example 6.

[0036] Figure 3 This is a graph showing the relationship between the electromagnetic shielding performance and resistivity of Examples 2-4.

[0037] Figure 4 This is the thermogravimetric curve of Example 4 in an air environment.

[0038] Figure 5 This is a scanning electron microscope image of Example 4.

[0039] Figure 6 This is a scanning electron microscope image of Example 7.

[0040] Figure 7 This is a comparison chart of the electromagnetic shielding performance of Example 2 and Example 8. DETAILED DESCRIPTION

[0041] In order to facilitate the understanding of the technical solution of the present invention, a novel carbonized polybenzoxazine aerogel and a preparation method thereof are further described below in conjunction with specific embodiments.

[0042] The experimental equipment used in the following examples is:

[0043] Magnetic stirrer, model 78-1, produced by Changzhou Xinxin Experimental Instrument Co., Ltd.; box-type heating furnace, model KSL-1200X, produced by Hefei Kejing Material Technology Co., Ltd.; tubular heating furnace, model GSL-1700X, produced by Hefei Kejing Material Technology Co., Ltd.; electric blast drying oven, Shanghai Lichenbang Instrument Technology Co., Ltd., model FX101-1, produced by Shanghai Shuli Instrument Co., Ltd.; constant temperature stirrer, model DF-101S, produced by Shanghai Lichenbang Instrument Technology Co., Ltd.; contact angle meter, model FCA20000A3E, produced by Shanghai Aifeis Precision Instrument Co., Ltd.; microcomputer-controlled electronic universal testing machine, model CMT6503, produced by Meters Industrial Systems (China) Co., Ltd.

[0044] Embodiment 1: Preparation method of novel carbonized polybenzoxazine aerogel:

[0045] Dissolve 10g of bisphenol F type benzoxazine monomer in 40g of N,N-dimethylformamide solvent, and place the mixed solution in an oven at 80 degrees Celsius for 12 hours to obtain a gel solution; dissolve 0.5-5g of hydrochloric acid in 40g of N,N-dimethylformamide solvent to obtain an acid catalytic solution, and then evenly mix the two solutions to obtain a polybenzoxazine solution;

[0046] The polybenzoxazine solution is poured into a mold to form a wet gel; then the wet gel is aged at room temperature for 10-20 hours, and then the wet gel is dried at normal pressure for 24 hours, and then the wet gel is washed with N,N-dimethylformamide 1-3 times, each washing time is 10-20 hours, to obtain a wet conductive gel; the wet conductive gel is then dried at room temperature and pressure for 24-48 hours to obtain a new polybenzoxazine aerogel with conductivity and electromagnetic shielding properties; finally, the dried new polybenzoxazine aerogel is heated in an argon environment at 800°C for 6 hours to obtain a new carbonized polybenzoxazine aerogel, whose electromagnetic shielding properties are shown in Table 2, the resistivity values ​​are shown in Table 3, and the specific surface area and average pore size are shown in Table 4.

[0047] Embodiment 2: Preparation method of novel carbonized polybenzoxazine aerogel:

[0048] 20g of bisphenol F type benzoxazine monomer was dissolved in 40g of N,N-dimethylformamide solvent, and the mixed solution was placed in an oven at 80 degrees Celsius for 12 hours to obtain a gel solution; 0.5-5g of hydrochloric acid was dissolved in 40g of N,N-dimethylformamide solvent to obtain an acid catalytic solution, and the two solutions were evenly mixed to obtain a polybenzoxazine solution; the polybenzoxazine solution was poured into a mold to form a wet gel; the wet gel was aged at room temperature for 10-20 hours, and then the wet gel was dried at normal pressure for 24 hours, and then the wet gel was The gel is washed with N,N-dimethylformamide for 1-3 times, each washing time is 10-20 hours, to obtain a wet conductive gel; the wet conductive gel is then dried at room temperature and pressure for 24-48 hours to obtain a novel polybenzoxazine aerogel having conductivity and electromagnetic shielding properties; finally, the dried novel polybenzoxazine aerogel is heated in an argon gas environment at 800°C for 6 hours to obtain a novel carbonized polybenzoxazine aerogel, the electromagnetic shielding properties of which are shown in Table 2, the resistivity values ​​are shown in Table 3, and the specific surface area and average pore size are shown in Table 4.

[0049] Embodiment 3: Preparation method of novel carbonized polybenzoxazine aerogel:

[0050] 30g of bisphenol F type benzoxazine monomer was dissolved in 40g of N,N-dimethylformamide solvent, and the mixed solution was placed in an oven at 80 degrees Celsius for 12 hours to obtain a gel solution; 0.5-5g of hydrochloric acid was dissolved in 40g of N,N-dimethylformamide solvent to obtain an acid catalytic solution, and the two solutions were evenly mixed to obtain a polybenzoxazine solution; the polybenzoxazine solution was poured into a mold to form a wet gel; the wet gel was aged at room temperature for 10-20 hours, and then the wet gel was dried at normal pressure for 24 hours, and then the wet gel was The gel is washed with N,N-dimethylformamide for 1-3 times, each washing time is 10-20 hours, to obtain a wet conductive gel; the wet conductive gel is then dried at room temperature and pressure for 24-48 hours to obtain a novel polybenzoxazine aerogel having conductivity and electromagnetic shielding properties; finally, the dried novel polybenzoxazine aerogel is heated in an argon gas environment at 800°C for 6 hours to obtain a novel carbonized polybenzoxazine aerogel, the electromagnetic shielding properties of which are shown in Table 2, the resistivity values ​​are shown in Table 3, and the specific surface area and average pore size are shown in Table 4.

[0051] Embodiment 4: Preparation method of novel carbonized polybenzoxazine aerogel:

[0052] 40 g of bisphenol F type benzoxazine monomer was dissolved in 40 g of N,N-dimethylformamide solvent, and the mixed solution was placed in an oven at 80 degrees Celsius for 12 hours to obtain a gel solution; 0.5-5 g of hydrochloric acid was dissolved in 40 g of N,N-dimethylformamide solvent to obtain an acid catalytic solution, and the two solutions were uniformly mixed to obtain a polybenzoxazine solution; the polybenzoxazine solution was poured into a mold to form a wet gel; the wet gel was aged at room temperature for 10-20 hours, and then the wet gel was dried at normal pressure for 24 hours, and then the wet gel was washed with N , N-dimethylformamide is used for cleaning 1-3 times, each cleaning time is 10-20 hours, to obtain a wet conductive gel; the wet conductive gel is then dried at room temperature and pressure for 24-48 hours to obtain a novel polybenzoxazine aerogel with conductivity and electromagnetic shielding performance; finally, the dried novel polybenzoxazine aerogel is heated in an argon gas environment at 800°C for 6 hours to obtain a novel carbonized polybenzoxazine aerogel, the residual carbon rate of which is shown in Table 1, the electromagnetic shielding performance of which is shown in Table 2, the resistivity value is shown in Table 3, and the specific surface area and average pore size are shown in Table 4.

[0053] The electromagnetic shielding performance of the products of Examples 1-4 was measured by a 3671G vector network analyzer and a waveguide method; the electromagnetic shielding performance comparison diagram is shown in FIG. Figure 1 As shown, with the increase of bisphenol F polybenzoxazine content, the electromagnetic shielding performance of the prepared new carbonized polybenzoxazine aerogel is improved.

[0054] The thermogravimetric curve of the novel carbonized polybenzoxazine aerogel prepared in Example 4 was measured using a TGA / DSC 3+ thermogravimetric analyzer (Mettler Toledo, Switzerland). The specific method is: the sample is placed in a special crucible according to the instrument manual, and the instrument records the loss mass in real time during the heating process. The thermogravimetric curve can be obtained by plotting the data through origin. The thermogravimetric curve of the novel carbonized polybenzoxazine aerogel prepared in Example 4 is shown in FIG. Figure 4 The carbonization temperature and residual carbon rate of the novel carbonized polybenzoxazine aerogel prepared in Example 4 are shown in Table 1.

[0055] Table 1 Carbon Residue Test Results

[0056]

[0057]

[0058] It can be seen from the data in Table 1 that the novel carbonized polybenzoxazine aerogel prepared in Example 4 has a relatively high high-temperature residual carbon rate and can be used in an environment of 400° C. or below.

[0059] The novel carbonized polybenzoxazine aerogel prepared in Example 4 was scanned by a SU8010 scanning electron microscope (HITACHI, Japan) under gold spraying test conditions. The scanning electron microscope image of Example 4 is shown in FIG. Figure 5 As shown by Figure 5 It can be seen that when the content of bisphenol F polybenzoxazine is within 10-40g, the prepared new carbonized polybenzoxazine aerogel has a normal gel structure.

[0060] The electromagnetic shielding performance of the novel carbonized polybenzoxazine aerogel prepared in Examples 2 to 4 was measured by a 3671G vector network analyzer using a waveguide method; the resistivity was measured using a four-probe method; the relationship between the electromagnetic shielding performance and the resistivity of Examples 2 to 4 is shown in the figure Figure 3 As shown, with the increase of bisphenol F polybenzoxazine content, the conductivity of the prepared new carbonized polybenzoxazine aerogel increases.

[0061] In order to better illustrate the beneficial effects of the present invention, the inventors of the present application modified the parameters of Examples 1-4 to form Examples 5-9 as comparative examples. The specific operations are shown in the preparation methods of Examples 5-9.

[0062] Embodiment 5: Preparation method of polybenzoxazine aerogel:

[0063] 50g of bisphenol F type benzoxazine monomer was dissolved in 40g of N,N-dimethylformamide solvent, and the mixed solution was placed in an oven at 80°C for 12 hours to obtain a gel solution; 0.5-5g of hydrochloric acid was dissolved in 40g of N,N-dimethylformamide solvent to obtain an acid catalytic solution, and the two solutions were evenly mixed to obtain a polybenzoxazine solution; the polybenzoxazine solution was poured into a mold to form a wet gel; the wet gel was aged at room temperature for 10-20 hours, and then the wet gel was dried at normal pressure for 24 hours, and then the wet gel was washed with N,N-dimethylformamide for 1-3 times, each washing time was 10-20 hours, to obtain a wet gel; the wet gel was then dried at room temperature and pressure to obtain a polybenzoxazine aerogel, and its electromagnetic shielding properties are shown in Table 2, and the resistivity values ​​are shown in Table 3.

[0064] Embodiment 6: Preparation method of polybenzoxazine aerogel:

[0065] 50g of bisphenol F type benzoxazine monomer was dissolved in 40g of N,N-dimethylformamide solvent, and the mixed solution was placed in an oven at 80°C for 12 hours to obtain a gel solution; 0.5-5g of hydrochloric acid was dissolved in 40g of N,N-dimethylformamide solvent to obtain an acid catalytic solution, and the two solutions were evenly mixed to obtain a polybenzoxazine solution; the polybenzoxazine solution was poured into a mold to form a wet gel; the wet gel was aged at room temperature for 10-20 hours, and then the wet gel was dried at normal pressure for 24 hours, and then the wet gel was washed with N,N-dimethylformamide 1-3 times, each washing time was 10-20 hours, to obtain a wet gel; the wet gel was then dried at room temperature and pressure; finally, the dried aerogel was heated in air at 200°C for 6 hours to obtain a polybenzoxazine aerogel, and its electromagnetic shielding performance is shown in Table 2, and the resistivity value is shown in Table 3.

[0066] The electromagnetic shielding performance comparison diagram of Example 4, Example 5 and Example 6 is as follows: Figure 2 As shown, Examples 5 and 6 are polybenzoxazine aerogels dried at room temperature and 200 degrees Celsius in air, without carbonization treatment. Compared with Example 4, it can be seen that the electromagnetic shielding performance of the aerogel is greatly enhanced after carbonization treatment at 800 degrees Celsius.

[0067] Embodiment 7: Preparation method of polybenzoxazine solid with higher density:

[0068] 60g of bisphenol F type benzoxazine monomer is dissolved in 40g of N,N-dimethylformamide solvent, and the mixed solution is placed in an oven at 80 degrees Celsius for 12 hours to obtain a gel solution; 0.5-5g of hydrochloric acid is dissolved in 40g of N,N-dimethylformamide solvent to obtain an acid catalytic solution, and the two solutions are evenly mixed to obtain a polybenzoxazine solution; the polybenzoxazine solution is poured into a mold to form a wet gel; the wet gel is aged at room temperature for 10-20 hours, and then the wet gel is dried at normal pressure for 24 hours, and then the wet gel is washed with N,N-dimethylformamide 1-3 times, each washing time is 10-20 hours, to obtain a conductive wet gel; the conductive wet gel is then dried at room temperature and pressure; finally, the dried aerogel is heated in an argon gas environment at 800°C for 6 hours to obtain a polybenzoxazine solid with a higher density.

[0069] The product of Example 7 was scanned under the electron microscope scanning conditions of the product of Example 4, and the scanning electron microscope image is as follows: Figure 6 As shown by Figure 5 and Figure 6 It can be seen that when the bisphenol F polybenzoxazine content is within 10-40g, the prepared polybenzoxazine aerogel has a normal gel structure; however, as the bisphenol F polybenzoxazine content increases, the final content is 60g and the gel structure is lost, turning into a polybenzoxazine polymer.

[0070] Embodiment 8: Preparation method of polybenzoxazine aerogel:

[0071] 20g of bisphenol-type benzoxazine monomer is dissolved in 40g of N,N-dimethylformamide solvent, and the mixed solution is placed in an oven at 80 degrees Celsius for 12 hours to obtain a gel solution; 0.5-5g of hydrochloric acid is dissolved in 40g of N,N-dimethylformamide solvent to obtain an acid-catalyzed solution, and the two solutions are evenly mixed to obtain a polybenzoxazine solution; the polybenzoxazine solution is poured into a mold to form a wet gel; the wet gel is aged at room temperature for 10-20 hours, and then the wet gel is dried at normal pressure for 24 hours, and then the wet gel is washed with N,N-dimethylformamide, acetonitrile, n-pentane and acetone for 1-3 times, each washing time is 10-20 hours, to obtain a wet gel; the wet gel is then dried at room temperature and pressure; finally, the dried aerogel is heated in an argon gas environment at 800 degrees Celsius to obtain a polybenzoxazine aerogel.

[0072] The electromagnetic shielding performance comparison diagram of Example 2 and Example 8 is as follows: Figure 7 As shown, the aerogel obtained by the preparation method of the present application has stronger electromagnetic shielding performance than the preparation method of CN113603925A (the method of Example 8).

[0073] Embodiment 9: Preparation method of polybenzoxazine aerogel:

[0074] 20g of bisphenol-type benzoxazine monomer is dissolved in 40g of N,N-dimethylformamide solvent, and the mixed solution is placed in an oven at 80 degrees Celsius for 12 hours to obtain a gel solution; 0.5-5g of hydrochloric acid is dissolved in 40g of N,N-dimethylformamide solvent to obtain an acid-catalyzed solution, and the two solutions are evenly mixed to obtain a polybenzoxazine solution; the polybenzoxazine solution is poured into a mold to form a wet gel; the wet gel is aged at room temperature for 10-20 hours, and then the wet gel is dried at normal pressure for 24 hours, and then the wet gel is washed with N,N-dimethylformamide and acetone for 1-3 times, each washing time is 10-20 hours, to obtain a gel; and the gel is supercritically dried with carbon dioxide to obtain a polybenzoxazine aerogel.

[0075] Embodiment 10: Preparation method of polybenzoxazine aerogel:

[0076] 20g of bisphenol-type benzoxazine monomer is dissolved in 40g of N,N-dimethylformamide solvent, and the mixed solution is placed in an oven at 80 degrees Celsius for 12 hours to obtain a gel solution; 0.5-5g of hydrochloric acid is dissolved in 40g of N,N-dimethylformamide solvent to obtain an acid-catalyzed solution, and the two solutions are evenly mixed to obtain a polybenzoxazine solution; the polybenzoxazine solution is poured into a mold to form a wet gel; the wet gel is aged at room temperature for 10-20 hours, and then the wet gel is dried at normal pressure for 24 hours, and then the wet gel is washed with N,N-dimethylformamide and acetone for 1-3 times, each washing time is 10-20 hours, to obtain a gel; the gel is then supercritically dried with carbon dioxide to obtain a dry aerogel; and then it is heated to 200 degrees Celsius at normal pressure in an air atmosphere to obtain a polybenzoxazine aerogel.

[0077] The electromagnetic shielding performance of the products prepared in Example 1 to Example 8 was tested, and the results are shown in Table 2; the resistivity of the products prepared in Example 1 to Example 8 was tested, and the results are shown in Table 3;

[0078] Table 2 Electromagnetic shielding performance test results (12.4GHz)

[0079]

[0080] Table 3 Resistivity test results

[0081]

[0082] The specific surface area and average pore size of the products prepared in Examples 1 to 10 were measured using a Micromeritics ASAP 2020 specific surface area analyzer. The results are shown in Table 4. The product of Example 7 is not a gel structure and is therefore not listed in Table 4:

[0083] Table 4 Comparison of specific surface area and average pore size

[0084]

[0085]

[0086] It can be seen from the data in Table 2, Table 3, and Table 4 that since the specific surface area and average pore size of the novel polybenzoxazine aerogel of the present invention are smaller than those of other polybenzoxazine aerogels, the reflection loss of electromagnetic waves in the material is greater, and therefore the novel polybenzoxazine aerogel has stronger electromagnetic shielding performance than other aerogel materials.

[0087] Examples 1-4 are carbonized aerogels with different bisphenol F contents. It can be seen that within a certain range, the higher the bisphenol F content, the stronger the electromagnetic shielding performance of the carbonized aerogel. However, when the bisphenol F content is too high, such as when the bisphenol F content in Example 7 is 60 parts, the obtained polybenzoxazine polymer will lose its gel structure, increase the weight of the material, and reduce its flexibility.

[0088] Examples 5 and 6 are polybenzoxazine aerogels dried at room temperature and 200 degrees Celsius in air, without carbonization treatment. Figure 2 It can be seen that the electromagnetic shielding performance of aerogel is greatly enhanced after carbonization treatment at 800°C.

[0089] Example 8 is a novel polybenzoxazine aerogel obtained by other cleaning methods. Figure 7 It can be seen that the aerogel cleaned only with N,N-dimethylformamide has better electromagnetic shielding performance.

[0090] Examples 9 and 10 are novel polybenzoxazine aerogels obtained by supercritical carbon dioxide drying. Compared with Example 2, it can be seen that the aerogels obtained by normal temperature and pressure drying have smaller bet surface area and pore size, and have better electromagnetic shielding structure.

[0091] The above description is only a preferred embodiment of the present invention and does not impose any formal or substantial limitation on the present invention. Any technician familiar with the profession can make use of the technical contents disclosed above without departing from the scope of the technical solution of the present invention, and any slight changes, modifications and evolutions made by equivalent changes are all equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A novel carbonized polybenzoxazine aerogel, characterized by: The novel carbonized polybenzoxazine aerogel is prepared from the following raw materials in parts by weight: 10-40 parts of bisphenol F-type benzoxazine, 50-200 parts of N,N-dimethylformamide, and 0.5-5 parts of hydrochloric acid, wherein the concentration of the hydrochloric acid is 36%-38%. The novel carbonized polybenzoxazine aerogel has a specific surface area of ​​5.38-24.811 square meters per gram, an average pore diameter of 5.95-14.16 nanometers, a resistivity of 4.93-7.34 ohm·meters, and an electromagnetic shielding of 28.05-77.51 decibels for 8-12.4 GHz electromagnetic waves.

2. A method for preparing a novel carbonized polybenzoxazine aerogel, characterized in that: The preparation method comprises the following steps: (1) dissolving bisphenol F type benzoxazine in N,N-dimethylformamide and heating to obtain a bisphenol F solution; adding hydrochloric acid to N,N-dimethylformamide to obtain an acid catalytic solution; mixing the bisphenol F solution and the acid catalytic solution and stirring to obtain a polybenzoxazine solution; (2) placing the polybenzoxazine solution obtained in step (1) into a mold to form a wet gel; (3) aging the wet gel obtained in step (2), and drying at normal pressure for 24 hours after aging; (4) washing the aged wet gel obtained in step (3) with N,N-dimethylformamide to obtain a wet conductive gel; (5) drying the wet conductive gel obtained in step (4) at room temperature and pressure for 24-48 hours to obtain a novel polybenzoxazine aerogel having electrical conductivity and electromagnetic shielding properties; (6) The polybenzoxazine aerogel obtained in step (5) is heated to 800° C. in an argon environment at a heating rate of 5° C. / min. After heating to 800° C., the aerogel is kept at this temperature for 6 hours and then cooled in a furnace. During the heating and cooling in the furnace, the argon flow rate is ensured to be greater than 50 ml / min. After cooling, a novel carbonized polybenzoxazine aerogel is obtained.

3. The method for preparing a novel carbonized polybenzoxazine aerogel according to claim 2, characterized in that: In step (1), by weight, bisphenol F-type benzoxazine is 10-40 parts, N,N-dimethylformamide is 50-200 parts, and hydrochloric acid is 0.5-5 parts, and the concentration of hydrochloric acid is 36%-38%.

4. The method for preparing a novel carbonized polybenzoxazine aerogel according to claim 2, characterized in that: In step (1), 10-30 parts of bisphenol F type benzoxazine are placed in 20-40 parts of N,N-dimethylformamide, and heated in a heating box at 80° C. for 12 hours, and cooled to room temperature to obtain a bisphenol F solution; 2-5 parts of concentrated hydrochloric acid are added to 20-40 parts of N,N-dimethylformamide and uniformly stirred to obtain an acid catalytic solution; the acid catalytic solution is added to the bisphenol F solution and rapidly stirred for 30 seconds to obtain a polybenzoxazine solution.

5. The method for preparing a novel carbonized polybenzoxazine aerogel according to claim 2, characterized in that: In step (2), the gel time is greater than 15 minutes.

6. The method for preparing a novel carbonized polybenzoxazine aerogel according to claim 2, characterized in that: In step (3), the aging environment is normal temperature and pressure; the aging time is 12-24 hours.

7. The method for preparing a novel carbonized polybenzoxazine aerogel according to claim 2, characterized in that: In step (4), the wet gel is washed with N,N-dimethylformamide for 1-3 times, and each washing time is 10-20 hours.

8. A novel carbonized polybenzoxazine aerogel prepared by the preparation method according to claims 2-7.

9. The novel carbonized polybenzoxazine aerogel according to claim 8, characterized in that: The specific surface area of ​​the new carbonized polybenzoxazine aerogel is 5.38-24.811 square meters per gram, the average pore size is 5.95-14.16 nanometers, the resistivity is 4.93-7.34 ohm-meter, and the electromagnetic shielding of 8-12.4GHz electromagnetic waves is 28.05-77.51 decibels.

Citation Information

Patent Citations

  • Recyclable multifunctional dynamic covalent polymer aerogel material as well as preparation method and application thereof

    CN113402764A

  • Bisphenol F type ultrahigh-strength benzoxazine aerogel

    CN113603925A

  • Hydrophobic polybenzoxazine aerogel and preparation method thereof

    CN118005988A

  • Copolymer hybrid aerogels based on isocyanate - cyclic ether - clay networks

    EP3315529A1

  • Benzoxazine based copolymer aerogels

    US20190048164A1